1985
DOI: 10.1152/jappl.1985.58.5.1572
|View full text |Cite
|
Sign up to set email alerts
|

Patellar tendon matrix changes associated with aging and voluntary exercise

Abstract: Male rats maintained under constant environmental conditions were randomly assigned to nonrunner (NR) and voluntary exercise (R) groups. At 9 mo, voluntary exercise significantly increased muscle cytochrome c concentration and citrate synthase activity. Also, at the same age, R animals had significantly greater glycosaminoglycan concentration than NR, but no changes in dry weight and collagen concentration were significant. By age 28 mo, the R groups had reduced daily running by 70%, and elevation of tendon gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Our values for hydroxyproline content in control rats are in agreement with previous results published for tendons and other similar connective tissues (Takacs and Verzar, 1968;Vailas et al, 1985Vailas et al, , 1988. Although long term monitoring for hydroxyproline content during tendon degeneration and regeneration has never been clearly reported, we showed that the rapid loss of hydroxyproline coincides with the accumulation of PMNs and Ms, which supports the hypothesis that leukocytes phagocytose and digest collagen during the inflammatory phase.…”
Section: Effects Of Diclofenac On Tendon Inflammation and Regenerationsupporting
confidence: 92%
“…Our values for hydroxyproline content in control rats are in agreement with previous results published for tendons and other similar connective tissues (Takacs and Verzar, 1968;Vailas et al, 1985Vailas et al, , 1988. Although long term monitoring for hydroxyproline content during tendon degeneration and regeneration has never been clearly reported, we showed that the rapid loss of hydroxyproline coincides with the accumulation of PMNs and Ms, which supports the hypothesis that leukocytes phagocytose and digest collagen during the inflammatory phase.…”
Section: Effects Of Diclofenac On Tendon Inflammation and Regenerationsupporting
confidence: 92%
“…Collagen content of the patellar tendon (Haut et al 1992) and tail-tendon (Vogel 1983) in animals has been shown to decrease or increase (Vailas et al 1985) with age. In humans, we recently demonstrated that collagen concentration of the patellar tendon was 34 % lower in old men compared to that in young men (Couppe et al 2009).…”
Section: Tendon Collagen Contentmentioning
confidence: 99%
“…IL-1β is a potent pro-inflammatory cytokine produced mainly by macrophages in injured tissues and upregulates the expression of other inflammatory mediators, including COX-2, IL-6, MMP-1, and MMP-3. In fibroblasts, for example, IL-1β induces the expression of MMPs (Tewari et al, 1994;Alvares et al, 1995), which could initiate the degradation and remodeling of tissues (e.g., tendons) in response to mechanical loading (Vailas et al, 1985). COX-2 is a major marker of tissue inflammation (Gilroy et al, 1998;Lipsky, 1999) that converts arachidonic acid into prostaglandins, such as PGE 2 .…”
Section: Introductionmentioning
confidence: 99%